Functional Interactions Between lncRNAs/circRNAs and miRNAs: Insights Into Rheumatoid Arthritis - Han, Juan-Juan; Wang, Xue-Qiang; Zhang, Xin-An (Frontiers in Immunology, 2022)
Rheumatoid arthritis (RA) is one of the most common autoimmune diseases that affect synovitis, bone, cartilage, and joint. RA leads to bone and cartilage damage and extra-articular disorders. However, the pathogenesis of RA is still unclear, and the lack of effective early diagnosis and treatment causes severe disability, and ultimately, early death. Accumulating evidence revealed that the regulatory network that includes long non-coding RNAs (lncRNAs)/circRNAs (cirRNAs), micro RNAs (miRNAs), and messenger RNAs (mRNA) plays important roles in regulating the pathological and physiological processes in RA, thereby providing new strategies for its diagnosis and treatment. In this review, we comprehensively summarized the regulatory mechanisms of lncRNA/circRNA-miRNA-mRNA network and the potential roles of non-coding RNAs as biomarkers and therapeutic targets for the diagnosis and treatment of RA.